The subfamily Haplophthalminae (Isopoda, Oniscidea, Trichoniscidae) from Georgian caves (Caucasus), with descriptions of a new genus and two new species - Taiti, Stefano; Shavadze, Lado; Maghradze, Eter; Barjadze, Shalva (Zootaxa, 2026)
Five species of troglobiotic terrestrial isopods belonging to the subfamily Haplophthalminae, family Trichoniscidae, are reported from caves in Georgia. A new species in the genus Colchidoniscus (Colchidoniscus fissus Taiti & Shavadze sp. nov.) and a new genus and species (Imeretioniscus tricostatus Taiti & Shavadze gen. et sp. nov.) are described. The subspecies Colchidoniscus kutaissianus motenae Borutzky, 1974 is raised to species rank. Diagnostic characters and affinities of all taxa are discussed. A key to the species is also provided.